Current Status and Prospects of Genetic Resources of Native Chickens of Japan - Hideaki Takahashi (Animals)
The Japanese government established Japan Agriculture Standards (JAS) in 1999 for the production of chicken meat using native Japanese chicken breeds, abbreviated as ‘Jidori JAS’, for the effective use of native chickens. “Jidori” means “native chickens” in Japanese. The Jidori JAS has designated the Japanese chicken breeds that were established in Japan and/or imported before the end of the Meiji period (until 1912). According to the Jidori JAS, the percentage of native blood in chickens to be marketed as certified Jidori JAS must be 50% or more. This indicates that the Japanese government has permitted the commercial production of hybrid chickens under the Jidori JAS certification. Jidori JAS was introduced to increase the number of chicks available for fattening and improve the growth performance of Jidori JAS certified production. While farmers have to buy chicks from hatcheries each time they produce poultry, this ensures stable production, and the meat quality of the chicken remains consistent. It should be noted that Jidori JAS certification does not guarantee a specific flavor for Jidori meat products. Currently, marker-assisted selection for growth improvement has been successfully implemented in Japan for several Jidori JAS-certified chickens, enhancing their growth performance.